Learning vocabulary through songs : a study on the role of music in teaching english verbs - Nor Azrul Hardi bin Adzmi (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, 2019)
Music and songs have been used in learning language for a long time. Second language users of English have been exposed to songs that are rich in vocabulary items since they were young. Peters and Webb (2018) and Medina (cited in Maneshi, 2017) found that repetition of single word and multiword items within songs are effective types of second language input. This study aims to investigate how the use of songs can aid tertiary-level students to increase their verb vocabulary power and their understanding of English verbs in their efforts to acquire English as a new language. Two groups of diploma students from the Sultan Abdul Halim Muadzam Shah International Islamic University (UniSHAMS) were selected for the study. The students in the experimental group were given a pre-test prior to being exposed to songs that were rich in verbs during the lessons and then given a post-test after the lessons, while the control group did the same pre-test and post-test without being exposed to the songs during the lessons. The tests were then evaluated and the finding was that there were improvements in the experimental group's post-test marks compared to the control group. The paired t-tests conducted on those results found a statistically significant difference in the results of the experimental group. The present research recommends that language teachers of tertiary level students should explore the possibility of using English songs in classrooms to aid their students' learning and to motivate their students to use English songs as a learning aid rather than simply being songs that they enjoy listening to.